An effective iterated greedy algorithm for multi-AGVs dispatching problem in material distribution. Issue 1 (August 2021) - Zhang, Xujin; Sang, Hongyan; Li, Zhongkai; Li, Junqing; Guo, Hengwei
Abstract: In this paper, the dispatching problem for multi-AGVs in the matrix manufacturing workshop from the practical factories is optimized. The goal is to reduce the transportation cost, including the cost of AGVs, distance cost and time cost. In order to solve the problem, we develop a mixed integer linear programming model. Then, an effective iterative greedy algorithm (IG) is proposed. The nearest-neighbor-based heuristic is used to generate high-quality initial solutions. An effective gradient unload method is designed. For the local search stage, three efficient operators are proposed. Finally, examples for experiment come from Foxconn electronic company. Comprehensive evaluation shows that the performance of the proposed IG is significantly better than some existing algorithms in the literature.